Developing instrument to increase students' geometry ability based on Van Hiele level integrated with Riau Malay culture - Astri Wahyuni; Leo Adhar Effendi; Lilis Marina Angraini; Dedek Andrian (Graduate School, Universitas Negeri Yogyakarta, 2020)
The study aims to develop geometric instruments that can be used to improve geometry based on Van Hiele's cognitive level, which is integrated with Malay culture. This study's research design is the Research and Development (R D) proposed by Carson, which consists of several stages, namely: potential and problems, material collection, product design, product validity, product testing, product revision, and mass products. The subjects of this study were 65 students majoring in math education in the first semester. The test instruments were analyzed using Aiken's validity and Cronbach Alpha reliability. The trial analysis was analyzed using descriptive statistics to test students' abilities during three meetings. The data analysis showed that the test instruments were developed in valid and reliable categories. The instruments developed were descriptions in the valid and reliable categories. The instruments in the form of valid and reliable test descriptions can be used to obtain relevant data and improve geometric skills based on the Van Hiele Level, which is integrated with Malay Culture.